Війна і біобезпека в Україні - Тукало, М.А.; Ткачук, З.Ю.; Яненко, У.М. (Вісник НАН України, 2023)
У статті розглянуто прогноз епідеміологічної ситуації, яка може очікувати Україну після підриву Каховської ГЕС та обміління Каховського водосховища. Через руйнування медичної інфраструктури населенню потерпілих територій стало складніше отримати належну медичну допомогу,
особливо в разі ймовірного спалаху інфекцій. Забруднення водних ресурсів,
збільшення кількості безпритульних тварин, відсутність профілактичних заходів для запобігання виникненню спалахів захворювань — усе це
ставить гострий виклик перед фахівцями, які відповідають за біологічну
безпеку населення та військових. У статті наведено стислий перелік інфекційних захворювань, які вже реєструються на тимчасово окупованих
територіях і можуть поширитися з біженцями та безпритульними тваринами на інші території України. Проаналізовано також наслідки стресу,
якого зазнають українці під час війни, що може призвести до збільшення
випадків смертельних захворювань. The article provides a forecast of the epidemiological situation that may await Ukraine due to the explosion of the Kakhovka
HPP and shallowing of the Kakhovka Reservoir resulting in the destruction of a harmonious ecosystem: humans
↔ animals ↔ plants. Due to the destroyed medical infrastructure in the country, the population cannot receive
proper medical care in the event of an outbreak of infections. It is important to focus public opinion on the tragic epidemiological
situation in Ukraine. It is necessary to unite specialists from various fields to positively solve the problem and
ensure the health of the nation. The pollution of water resources, the increase in the number of homeless animals, the lack
of appropriate measures to prevent outbreaks of diseases — all this poses a sharp challenge to specialists who are responsible
for the biological safety of the state’s population and soldiers. The article presents a concise list of infectious diseases
that have already been registered in the temporarily occupied territories and can be brought with refugees and
homeless animals to the territory free from the occupiers. The consequences of the stress experienced by Ukrainians
during the war, which can lead to an increase in cases of fatal diseases, are also analyzed.